Correlations Between Life-Detection Techniques and Implications for Sampling Site Selection in Planetary Analog Missions - Gentry DM; Amador ES; Cable ML; Chaudry N; Cullen T; Jacobsen MB; Murukesan G; Schwieterman EW; Stevens AH; Stockton A; Tan G; Yin C; et al. (MARY ANN LIEBERT, INC, 2022)
We conducted an analog sampling expedition under simulated mission constraints to areas dominated by basaltic tephra of the Eldfell and Fimmvorouhals lava fields (Iceland). Sites were selected to be homogeneous at a coarse remote sensing resolution (10-100m) in apparent color, morphology, moisture, and grain size, with best-effort realism in numbers of locations and replicates. Three different biomarker assays (counting of nucleic-acid-stained cells via fluorescent microscopy, a luciferin/luciferase assay for adenosine triphosphate, and quantitative polymerase chain reaction (qPCR) to detect DNA associated with bacteria, archaea, and fungi) were characterized at four nested spatial scales (1m, 10m, 100m, and >1km) by using five common metrics for sample site representativeness (sample mean variance, group F tests, pairwise t tests, and the distribution-free rank sum H and u tests). Correlations between all assays were characterized with Spearman's rank test. The bioluminescence assay showed the most variance across the sites, followed by qPCR for bacterial and archaeal DNA; these results could not be considered representative at the finest resolution tested (1m). Cell concentration and fungal DNA also had significant local variation, but they were homogeneous over scales of >1km. These results show that the selection of life detection assays and the number, distribution, and location of sampling sites in a low biomass environment with limited a priori characterization can yield both contrasting and complementary results, and that their interdependence must be given due consideration to maximize science return in future biomarker sampling expeditions. Key Words: AstrobiologyBiodiversityMicrobiologyIcelandPlanetary explorationMars mission simulationBiomarker. Astrobiology 17, 1009-1021.